Analisa Lapisan Termoklin Musiman Di Perairan Indonesia (Studi Kasus Selat Malaka) - Hendra, Hendra; Pranowo, Widodo Setiyo; Umam, Choirul; Azhari, Ferian; Agustinus, Agustinus (Universitas Diponegoro, 2024)
The Malacca Strait is a strategic waterway for Indonesia as it serves as an international shipping route connecting East Asia with the Middle East and Europe. In addition, the Malacca Strait also has great potential for natural resources, such as oil and gas as well as fish and other marine products. This study aims to describe the Thermocline Layer in the Malacca Strait based on Marine Copernicus Data in 2020 with a depth of up to 1000 meters. The temperature data was visualized using ODV 5.5.2 software. The results of processing the Marine Copernicus Temperature Data in 2020 in the Malacca Strait with a depth of up to 1000 meters show that the thermocline boundary varies each season. In the western season, the thermocline boundary is at a depth between 11 meters to 131 meters, in the first transitional season, it is at a depth between 22 meters to 131 meters, in the eastern season, it is at a depth between 56 meters to 156 meters, and in the second transitional season, it is at a depth between 78 meters to 131 meters. Bagian Selat Malaka adalah perairan yang strategis bagi Indonesia karena menjadi jalur pelayaran internasional yang menghubungkan Asia Timur dengan Timur Tengah dan Eropa. Selain itu, Selat Malaka juga memiliki potensi sumber daya alam yang besar, seperti minyak dan gas bumi serta ikan dan hasil laut lainnya. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis Lapisan Termoklin di Perairan Selat Malaka berdasarkan Data Marine Copernicus tahun 2020 dengan kedalaman sampai 1000 meter. Data Temperatur diolah dan dianalisis menggunakan software ODV 5.5.2. Hasil pengolahan Data Temperatur Marine Copernicus tahun 2020 di Perairan Selat Malaka dengan kedalaman mencapai 1000 meter dengan batas termoklin setiap musim dimana pada Musim barat batas termoklin berada pada kedalaman antara 11 meter sampai dengan 131 meter, Musim Peralihan I batas termoklin berada pada kedalaman antara 22 meter sampai dengan 131 meter, Musim Timur batas termoklin berada peda kedalaman antara 56 meter sampai dengan 156 meter dan Musim Peralihan II batas termoklin berada pada kedalaman antara 78 meter sampai dengan 131 meter.